Programmed DNA elimination drives rapid genomic innovation in two thirds of all bird species - Ruiz-Ruano, Francisco J; Schlebusch, Stephen A; Vontzou, Niki; Moreno, Hugo; Biegler, Matthew T; Kutschera, Verena E; Ekman, Diana; Borges, Inês; Pei, Yifan; Rossini, Roberto; Albrecht, Tomas; Boman, Jesper; et al. (bioRxiv, 2025)
Bird genomes are among the most stable in terms of synteny and gene content across vertebrates. However, germline-restricted chromosomes (GRCs) represent a striking exception where programmed DNA elimination confines large-scale genomic changes to the germline. GRCs are known to occur in songbirds (oscines), but have been studied only in a few species of Passerides such as the zebra finch, the key model for passerine genomics. Their presence and evolutionary dynamics in most major passerine lineages remain largely unexplored, with suboscines entirely unexamined by cytogenetic or genomic methods. Here, we present the most comprehensive comparative analysis of GRCs to date, spanning 44 million years of passerine evolution. By generating the first germline reference genomes of an oscine and a suboscine, 22 novel germline draft genomes spanning nearly all major passerine lineages and a germline draft genome of a parrot outgroup, we show that the GRC is likely present in 6,700 passerine species. Our results reveal that the GRC evolves rapidly and distinctly from the standard A chromosomes (autosomes and sex chromosomes), yet retains functionally important, selectively maintained genes. We observed gene and repeat turnover occuring orders of magnitude faster than on the A chromosomes. Some GRC genes, such as cpeb1 and pim1, are widespread from an ancient duplication. In contrast, other GRC genes, like mfsd2b and bmp15, have been independently duplicated onto the GRC multiple times, suggesting adaptive constraints. The discovery of zglp1 on the zebra finch GRC, initially copied from chromosome 30 and subsequently lost from it, indicates functional replacement, where the GRC permits gene loss from the standard genome. As the GRC harbors the only zglp1 copy in most of the ~4000 Passerides species, GRC loss would compromise essential germline functions. Our findings establish the GRC as a genomic innovator driving rapid germline evolution. This fact highlights its evolutionary significance for passerine diversification and suggests that programmed DNA elimination may be an overlooked yet phylogenetically widespread mechanism in many understudied animal lineages.